Peran Pemerintah Daerah dalam Melakukan Perlindungan Hukum Terhadap Perusakan Hutan Mangrove Akibat Pengalihfungsian Lahan di Kabupaten Pamekasan - Dimas Agung Prasetya (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Mangroves naturally grow along the coast of Indonesia. Mangrove ecosystems are highly vulnerable to changes in land use, one of which is caused by increased levels of exploitation. One such occurrence is in Ambat Village, an area in Pamekasan Regency rich in mangrove ecosystems. Mangrove ecosystems play a crucial role in maintaining environmental sustainability and supporting the lives of surrounding communities. However, in recent years, the practice of mangrove clearing and land conversion in this area has become a very concerning issue. Mangrove land conversion occurs when areas previously dedicated to mangrove growth are converted to other uses, such as industrial infrastructure development. This study aims to determine the role of local governments in providing legal protection against mangrove forest destruction caused by land conversion. The findings obtained from this study are that supervision carried out by the government or related agencies in overseeing mangrove forests in the coastal area of Ambat Village, Pamekasan Regency, is currently ineffective. This is evident in the ongoing clearing of mangrove forests and the conversion of mangrove land in the area. To address this problem, it is necessary to develop policies that support sustainable mangrove land management.